2008
DOI: 10.1177/0267658308090186
|View full text |Cite
|
Sign up to set email alerts
|

Second language processing: when are first and second languages processed similarly?

Abstract: . Second language processing: when are first and second languages processed similarly?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
230
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(258 citation statements)
references
References 33 publications
24
230
3
1
Order By: Relevance
“…One possible explanation is that there might be differences in Dutch as opposed to German gender agreement processing-note that Sabourin and Stowe (2008) and Hagoort (2003) also did not observe a LAN for gender agreement violations between determiner and nouns (in midsentence position) in Dutch native speakers, whereas Gunter et al (2000) did observe a LAN for similar gender violations in Germans. If this was the case, our German participants might have transferred their German "processing mode" to Dutch.…”
Section: Gender Agreement Condition and The Role Of Incorrect Subjectmentioning
confidence: 77%
“…One possible explanation is that there might be differences in Dutch as opposed to German gender agreement processing-note that Sabourin and Stowe (2008) and Hagoort (2003) also did not observe a LAN for gender agreement violations between determiner and nouns (in midsentence position) in Dutch native speakers, whereas Gunter et al (2000) did observe a LAN for similar gender violations in Germans. If this was the case, our German participants might have transferred their German "processing mode" to Dutch.…”
Section: Gender Agreement Condition and The Role Of Incorrect Subjectmentioning
confidence: 77%
“…We expected gender agreement with these nouns to be more challenging for adult L2ers, based on previous studies (e.g., Foucart and Frenck-Mestre, 2012;Franceschina, 2005;Grüter et al, 2012;Meulman et al, 2016;Montrul et al, 2008;Sabourin, 2003;Sabourin and Stowe, 2008). Experiment 2 used a spot-the-difference task to examine similar dependencies (determiner-noun-adjective number and gender agreement) in elicited spoken production.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the lack of strong distributional cues to gender made it difficult for the L2ers in the Foucart and Frenck-Mestre study to retrieve gender information online, at least in contexts that can be considered more taxing (in line with Grüter et al, 2012 andHopp, 2013). Sabourin (2003) and Sabourin and Stowe (2008) Their results revealed that only the L1-German group showed robust offline knowledge of lexical gender (mean accuracy rate: 93%) and native-like processing for gender violations (i.e., P600). In contrast, both the L1-Romance and L1-English groups scored below 80% accuracy with offline gender assignment, and neither group showed native-like processing for gender violations.…”
Section: L2 Learnersmentioning
confidence: 99%
“…Our hypothesis was also based on several studies that showed that learners can come to process L2 structures in nativelike ways (e.g., Dussias, 2013;Osterhout et al, 2006;Osterhout et al, 2008;Sabourin & Stowe, 2008;Tokowicz & Warren, 2010) and on studies showing that metalinguistic information can help learners to process their L2 in more nativelike ways (Davidson & Indefrey, 2009). It should be reiterated that the use of ERPs and eye-tracking measures does not ensure that a particular structure is processed implicitly.…”
Section: How Explicit Knowledge Affects Online L2 Processing 29mentioning
confidence: 99%